Comparative study of antimicrobial action of aloe vera and antibiotics against different bacterial isolates from skin infection - Safia Arbab; Hanif Ullah; Wang Weiwei; Xiaojuan Wei; Salah Uddin Ahmad; Lingyu Wu; Jiyu Zhang (Veterinary Medicine and Science, 2021)
Abstract Aloe vera is reputed to have medicinal properties. For centuries, it has been used for an array of ailments such as mild fever, wounds and burns, gastrointestinal disorders, diabetes, sexual vitality and fertility problems to cancer, immune modulation, AIDS and various skin infections. In present study, antibacterial activity of aloe vera gel extracts was tested against some common skin infection pathogens, that is, Escherichia coli, Shigella, Salmonella spp. and Staphylococcus aureus all were recorded positive. Antibiotic resistance and susceptibility pattern of above isolates were also studied against 10 clinically significant antibiotics (ampicillin [AMC], amoxicillin, augmentin, cefotaxime, ceftazidime [CAZ], cefuroxime [CXM], ciprofloxaci, tetracycline, cefpodoxime and imipenem). AMC and CXM were found to be most effective antibiotic followed by CXM with highest efficacy against Gram‐negative bacteria. In case of CAZ showed highest efficacy was showed against Gram‐positive bacteria. Aloe vera leave gel was extracted with four different solvent‐like aloe vera leaf extract, root extract, leaf ethanol extract and root ethanol extract; however, Gram‐negative as well Gram‐positive isolates was found highest susceptibility with aloe leaf and aloe root ethanol extract. Moderate sensitivity observed with aloe leaf extract and aloe root extract against both Gram‐positive as well as Gram‐negative bacterial isolates. This result showed that ethanol extracts of aloe vera both leaf and root can be used alongside conventional antibiotics to fight agents of infections that are so prevalent in the skin infection.